Implementasi Pendidikan Karakter Peduli Lingkungan melalui Pembelajaran Pendidikan Lingkungan Hidup (PLH) di Sekolah Dasar Muhammadiyah Alam Surya Mentari Tahun Ajaran 2016/2017 - Rini, Erlina Fajar; , Drs. Saring Marsudi, SH. M.Pd (2017)
This study aims to describe the implementation of environment education, to know the supporting factors and obstacles in the implementation of learning, as well as to determine whether there is an increase in the character concerned about the environment on students through environment education. This research approach uses qualitative research with case study type. Data collection techniques used were interviews, observation and documentation. The results showed that the learning of environmental education in Primary School Muhammadiyah Alam Surya Mentari done with pretty good views of the stage of planning, organizing, implementation, and evaluation of, and supported by adequate infrastructure be a contributing factor in the implementation of learning, while of factors that should could soon be overcome. Environmental education has three successful achievement of targets that includes cognitive, affective, and psychomotor. Researchers observed that the implementation of character education environmental awareness through environmental education learning in Primary School Muhammadiyah Alam Surya Mentari Academic Year 2016/2017 are qualified and able to provide the effect of increased environmental awareness character.